The effect of phospho-peptide on the stability of gold nanoparticles and drug delivery - Hou, Zhanwu (J Nanobiotechnology, 2019)
BACKGROUND: Gold nanoparticles (AuNPs) have been proposed for many applications in medicine and bioanalysis. For use in all these applications, maintaining the stability of AuNPs in solution by suppressing aggregation is paramount. Herein, the effects of amino acids were investigated in stabilizing AuNPs by rationally designed peptide scaffolds. RESULTS: Compared to other tested amino acids, phosphotyrosine (pY) significantly stabilized AuNPs. Our results indicated that pY modified AuNPs presented a high level of stability in various solutions, and had good biocompatibility. When a pY-peptide was used in stabilizing AuNPs, the phosphate group could be removed by phosphatases, which subsequently caused the aggregation and the cargo release of AuNPs. In vitro study showed that AuNPs formed aggregation in a phosphatase concentration depending manner. The aggregation of AuNPs was well correlated with the enzymatic activity (R(2) = 0.994). In many types of cancer, a significant increase in phosphatases has been observed. Herein, we demonstrated that cancer cells treated with pY modified AuNPs in conjunction with doxorubicin killed SGC-7901 cells with high efficiency, indicating that the pY peptide stabilized AuNPs could be used as carriers for targeted drug delivery. CONCLUSION: In summary, pY peptides can act to stabilize AuNPs in various solutions. In addition, the aggregation of pY-AuNPs could be tuned by phosphatase. These results provide a basis for pY-AuNPs acting as potential drug carriers and anticancer efficacy. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12951-019-0522-y) contains supplementary material, which is available to authorized users.